SQL server analysis services 2012 cube development cookbook more than 100 recipes to develop business intelligence solutions using analysis services - Dewald, Baya (Quick answers to common problems, 2013)
A practical cookbook packed with recipes to help developers produce data cubes as quickly as possible by following step by step instructions, rather than explaining data mining concepts with SSAS. If you are a BI or ETL developer using SQL Server Analysis services to build OLAP cubes, this book is ideal for you. Prior knowledge of relational databases and experience with Excel as well as SQL development is required.